Hydrodynamic effects asociated to methyl ester sulphonation in falling film reactors (2013)
Falling film reactors (FFR) are widely used in industry, mainly in those processes which require an efficient heat exchange. Although, these devices have been studied for several years, there is not yet a full understanding of their behavior. This is due to the fact that the performance of the FFRs can be easily influenced by hydrodynamic factors which affect transport phenomena in the reactor. In this study, an experimental analysis of hydrodynamic factors influencing a FFR is presented, paying special attention to hydrodynamic phenomena such as the phases’ flow regimens and the residence time for the sulphonation of methyl ester (ME) from palm oil with SO3. The results show that along with the SO3/ME ratio the hydrodynamic of both phases (gas and liquid) present in the reactor have a strong influence over the sulphonation efficiency